Influence of National Culture on Entrepreneurial Orientation: an International Comparison - Ho, Sing Foong (2008)
This research endeavours to examine the influence of culture on entrepreneurial orientation (EO) at a national level. National cultures are perceived to affect the behaviours and attitudes of individuals hence their tendencies towards entrepreneurial activities, which has led us to the mentioned research topic. Using Hofstede's theory of national culture as a basis, it is proposed that countries in which power distance, uncertainty avoidance and long-term orientation are low while simultaneously exhibiting high level of individualism and masculinity; its overall entrepreneurial behaviours tend to be more vigorous. Culture scores are readily adopted from Hofstede's literatures and the EO of the researched nations are determined via interpretation of their overall R&D and patenting activities. Research results have indicated that national culture has weak implications on EO and expected economic structure, political conditions and government policies to also play essential roles in leveraging EO. Implications of this research are discussed extensively and put into an organisational perspective for a more practical view of such relationship and its limitations are described to aid further research.